Desain Produk Cenderamata Berbasis Konsep Metafora dari Konservasi Penyu di Sindu Dwarawati Turtle Conservation - I Komang Ananta Pradnya Wikarna (Fakultas Industri Kreatif Universitas Surabaya, 2024)
This study describes the process of designing souvenir products based on the metaphorical concept derived from the conservation of green turtles at Sindu Dwarawati Turtle Conservation, Sindu Beach, Sanur, Denpasar. The metaphorical concept serves as the foundation for capturing the form and anatomical characteristics of the green turtle to design products that are not only aesthetically pleasing but also carry profound meaning in the context of environmental conservation. Qualitative methods were employed, involving direct interviews with the Chairman of Sindu Dwarawati Turtle Conservation, I Made Winarta, and direct observations at the conservation site. The gathered data focused on the conservation values of turtles, the characteristics of green turtles, and the design preferences for souvenir products that appeal to tourists and local residents. The outcome was an interactive keychain design that integrates the carapace pattern and four limbs of the green turtle as its primary inspiration. This keychain serves not only as a visually appealing souvenir but also as an educational tool highlighting the dangers of plastic waste to the survival of turtles. Through this design, it is hoped to increase public awareness and interest in visiting turtle conservation sites